AN ERROR ANALYSIS ON THE STUDENTS’ RECOUNT TEXT WRITING, A CASE STUDY AT THE FIRST CLASS OF WASKITO SENIOR HIGH SCHOOL - Sunardi, Sunardi (Lexeme : Journal of Linguistics and Applied Linguistics, 2023)
The study aims to conduct error Analysis on the  studentsâ€™ recount text writing, a  case study at the first  class  of  Waskito Senior High School. It focuses to get empirical data and to analyze the writing errors made by the students. It is qualitative research with descriptive methods. The subject of the research is the  first class students of  Waskito Senior High School. While the instrument used  is taken from  students recount text  writing assignment. There are four steps in analyzing the errors, namely identification, description, explanation, and evaluation.  The grammatical errors that appear in the students writing are analyzed  by using  the  Surface Strategy Taxonomy proposed by Dulay;  (1) omission, (2) addition, (3) miss- selection, (4) miss-ordering. The finding showed that the total of errors is 170 items   and  they indicated that the most  errors were   miss- selection  (52.3%) and followed by omission (44.1%), addition (2.3%) and miss-ordering (1.1%). Based on the results, it can be concluded that students still  have grammatical  difficulties in writing recount text. It is hoped it will be beneficial for the parties who involve in educational institution   such as English teachers, lectures, students, and other educational practitioners.  The writer suggests that the students need to learn more intensively about past tense in recount text, especially the change of verb form both in regular and irregular verbs, as well as the use of auxiliary verbs.